Diversity and Performance - Li, Feng; Nagar, Venky (Management Science, 2013)
This study measures the performance of U.S. firms initiating same-sex domestic partnership benefit (SSDPB) policies. The results show that holding these firms upon their SSDPB initiation in a calendar portfolio earns a four-factor annualized excess return (alpha) of approximately 10% over the 1995–2008 sample period, beating 95% of all professional mutual funds in the United States. This finding is robust to several tests of reverse causality. SSDPB adopters also show significant improvement in operating performance relative to nonadopters. This paper was accepted by Brad Barber, finance.